The Model of the Sustainability of E-commerce Adoption: A Study on Carved Furniture SMEs in Indonesia - Miftahurrohman, Miftahurrohman; Sediyono, Eko; Nugraha, Albert Kriestian Novi Adhi (Technium Social Sciences Journal, 2022)
The extent of e-commerce use by SMEs in developing countries such as Indonesia is still relatively low. This study seeks to identify and test the sustainability factors of e-commerce use by SMEs in a developing country. This study uses TOE theory which was expanded by including 12 predictors of sustainability of e-commerce adoption into four sub-domains: technology, organization, environment, and psychology. The contribution of this study is to explain the relevance of predictors of e-commerce adoption differs across two-time phases: at the early adoption phase and the later phase. In particular, in the early adoption phase, competitive pressure is a variable that affects the sustainability of e-commerce adoption. While at the later phase, perceived trust and competitor pressure are predictors that affect the sustainability of e-commerce adoption. Another interesting finding from this study is that SMEs utilize online sales brokers to increase their production and sales. This is done by SMEs, because they are aware of the limited resources that SMEs have.